Telitacicept administration improved immunoglobulin A nephropathy after hematopoietic stem cell transplantation: a case report - Yuan, Zishu; Dong, Dan; Zhang, Li; Xu, Zhonggao (Frontiers in Medicine, 2025)
BackgroundTelitacicept is a biologic that specifically targets B-lymphocyte stimulator and a proliferation-inducing ligand, demonstrating significant potential for therapeutic applications in B-cell-mediated autoimmune diseases. Currently, telitacicept is primarily utilized in the treatment of systemic lupus erythematosus. However, its therapeutic effect on immunoglobulin A nephropathy (IgAN) after hematopoietic stem cell transplantation (HSCT) has not been reported. This case report presents the clinical outcome of telitacicept administration in the treatment of IgAN following HSCT.Case reportA 36-year-old Asian man developed IgAN following allogeneic HSCT for acute myeloid leukemia (AML). The patient presented with features of high-risk nephrotic syndrome, including a urinary protein quantification of 8.28 g/24 h and serum albumin level of 29 g/L. The patient showed significant clinical improvement following treatment with moderate-dose glucocorticoids combined with telitacicept. After the treatment process, the urine albumin quantification decreased to 0.23 g/24 h, and serum albumin increased to 45.8 g/L. During the treatment, estimated glomerular filtration rate (eGFR) increased from 67.3 to 79.83 mL/min/1.73m2, and immune indicators immunoglobulin A (IgA), immunoglobulin G (IgG) and immunoglobulin M (IgM) also demonstrated steady levels (IgA: 6.78–10.1 g/L, IgG: 0.5–1.41 g/L, IgM: 0.17–0.6 g/L). Notably, the patient’s condition remained stable without any significant adverse effects throughout the rapid tapering of the glucocorticoid dose.ConclusionThis case suggests that telitacicept may be an effective treatment option for IgAN following HSCT, providing valuable insights into future therapeutic strategies for managing post-HSCT IgAN.